163k views
1 vote
F(x) = x + 6f(x) = x - 6What’s the answers

User Eddie Awad
by
4.4k points

1 Answer

1 vote

Question:

Solution:

Consider the following function:


f(x)\text{ = x+6}

this is equivalent to:


y\text{ = x+6}

solving for x, we get:


x\text{ = y - 6}

exchanging the notation we get:


f(x)\text{ = x- 6}

The same procedure is applied analogously for the function f(x) = x-6.

We can conclude that the correct answer is:

YES

F(x) = x + 6f(x) = x - 6What’s the answers-example-1
User Erick R Soto
by
4.8k points